PENGGUNAAN METODE TREE SAMPLING DALAM PENDUGAAN STRUKTUR TEGAKAN, BERAT BASAH DAN VOLUME TEGAKAN GAMAL (Gliricidia sepium): The Use of Tree Sampling Methods in Estimating Stand Structure, Wet Weight and Volume Gamal (Gliricidia sepium) Stands (Jurnal ForestrIndo, 2025)
This study aims to evaluate the application of the tree sampling method in estimating the stand structure and wet weight of gamal trees (Gliricidia sepium) as a source of biomass energy. Data collection was carried out in three age class plots (2019, 2020, and 2021) in the RPH Hanjuang Barat, BKPH Lengkong, KPH Sukabumi. Stand structure was obtained through census and tree sampling simulation with variations in the number of sample trees (9, 12, and 15) and sample points (5 and 7). The chi-square test results showed that the tree sampling method with 12 and 15 sample trees at 5 points and 9, 12, and 15 sample trees at 7 points was able to estimate the stand structure that was close to the actual conditions. Estimates of wet weight, and stand volume showed the highest values in the 2019 planting year with 15 sample trees and 7 points, amounting to 81.084 tons ha⁻¹, and 182.650 m³ ha⁻¹, respectively. These results indicate that stand age, number of sample trees, and sampling points affect estimation accuracy. The tree sampling method can potentially be an efficient alternative for biomass stand inventory.